DOSE AND SAFETY OF HYPOETES POLYTHYRSA MIQ ETHANOL EXTRACT FOR DISSOLVING RENAL CALCULI: an affordable medication - K, Widana; I G. M., Adioka; D. K., Ernawati (Udayana University, 2012)
Renal calculi develops when the urine contains more crystal-forming substances, such as calcium, uric acid and a compound called oxalate. Most renal calculis are calcium-based, usually in combination with oxalate. Hypoetes Polythyrsa Miq has been used empirically to prevent or treat renal calculi. This study aims to identify toxicity or side effect of Hypoetes Polythyrsa Miq ethanol extract for dissolving renal calculi, therefore this extract can be applied safely and effective for curing renal calculi. An in vitro research with pre-post control group design was conducted at Pharmacy Department Faculty of Medicine Udayana University. In addition, to determine as to whether the extract is safe orally, LD50 test was also conducted using mice strain BALB/c. The results showed that ethanol extract of Hypoetes Polythyrsa Miq leaves has dissolved renal calculi significantly (? <0.05). Five percent of the extract was effectively dissolving calcium stone 3.36 times higher than control positive (BE). It was also proven that an acute LD50 was achieved at a dose of 0.694 g extract (139% of usual dose). It can be concluded that the use of ethanol extract per oral in short term therapy is safe. Keywords: traditional medicine, hypoetes polythyrsa Miq, renal calculi.